Vitamin D status in Kancheepuram District, Tamil Nadu, India - John Mechenro; Giriprasad Venugopal; M. Buvnesh Kumar; D. Balakrishnan; Balakrishnan S. Ramakrishna (BMC, 2018)
Abstract Background Vitamin D has multifarious roles in maintenance of health and prevention of disease. The present study was undertaken to assess the vitamin D status of a rural adult south Indian population and to identify its associations with socioeconomic status and cultural practices. Methods Between June 2015 and July 2016, 424 healthy adults residing in Kattankulathur block in Tamil Nadu, India, provided venous blood samples and answered questions by personal interview. 25-hydroxy vitamin D was estimated by ELISA. Results Fifty nine (13.9%) of the 424 participants had 25OHD levels below 12 ng/mL (vitamin D deficient) and 175 (41.3%) had 25OHD levels between 12 to 20 ng/mL (vitamin D insufficiency). In univariate analysis, demographic factors associated with vitamin D status included education, occupation, socioeconomic class, and birthplace; lifestyle factors included sun exposure time, skin surface exposed to sunlight, use of sunscreen, awareness of vitamin D, and consumption of fish; and hygiene related factors included source of drinking water, availability of tap water at home, and closed toilet at home. In ordinal logistic regression, the following variables were found to be independently associated with vitamin D sufficiency: Duration of daily sun exposure below 30 min (Odds ratio 0.31, 95% confidence intervals 0.14-0.71, P = 0.006), sun exposure 30-60 min (OR 0.49, 95% CI 0.30-0.80, P = 0.004), male gender (OR 2.00, 95% CI 1.30-3.09, P = 0.002), higher level of education (OR 0.80, 95% CI 0.69-0.94, P = 0.005), non-consumption of fatty fish (OR 0.48, 95% CI 0.24-0.85, P = 0.035) and presence of closed toilet system at home (OR 0.59, 95% CI 0.37-0.93). Conclusion VDD and VDI are highly prevalent in this rural Indian community. The study identifies socioeconomic and behavior patterns that negatively impact vitamin D sufficiency, thus providing a basis for targeted intervention.